Relasi Kuasa Michel Foucault dalam Kanonisasi Ibnu Mujahid - Saifiddaulah Saifiddaulah (Wahana Islamika Jurnal Studi Keislaman, 2026)
This study examines the science of Qira’at, the variations in Qur’anic recitation. The author is interested in revisiting the authenticity of qira’at. The uncertainty and controversy surrounding the authenticity of qira’at, whether presented by Western or Muslim scholars, make this topic even more compelling to study in depth using the framework of Michel Foucault's theory of power relations, which itself originates from the West. This study aims to fill the knowledge gap by exploring the history of standardization and canonization of qira’at carried out by Ibn Mujahid in establishing seven imams as authorities in the canonization of the seven canonical qira’at. Consequently, it formulates several questions, namely why Ibn Mujahid standardized Qira’at in his book As-Sab’ah; what indicators Ibn Mujahid used to evaluate qira’at; and what political context underlies the canonization of qira’at by Ibn Mujahid. The results of this study indicate that the success of the codification and canonization of qira’at by Ibn Mujahid was not only due to the factor of unifying the views of Muslims regarding the different variants of Qur’anic readings, but was also influenced by the political factors underlying the process. These findings provide new insights into understanding the dynamics of the history of Qur’anic qira’at and the importance of considering the political context in understanding religious traditions.